Hypovitaminosis D in university workers in Southern Ecuador: interactions between gender and lifestyle - Díaz, Patricia; Cadena, Marcela; Montalván, Martha Elena; Garrochamba, Kleber; Calderón, Paula; Carrión, Gloria; Santana, Sergio (Frontiers in Nutrition, 2024)
Background Hypovitaminosis D may be common in tropical countries and is linked to disorders of phospho-calcium metabolism, rickets, muscle pain, immune system deficiencies, and increased susceptibility to microbial infections. Objective: To assess the prevalence of hypovitaminosis D in apparently healthy university workers in Loja, Ecuador. Methods: A cross-sectional study was completed in a private Ecuadorian university from May 2023 to September 2023, involving 440 participants. Data were gathered using a structured questionnaire created to assess risk factors influencing vitamin D levels. Serum 25-hydroxyvitamin D (25-OH)D concentrations were measured utilizing immunoenzymatic methods. Altered states (insufficiency or deficiency) of vitamin D were defined with serum values < 30 ng/mL. Associations between vitamin D status and selected determinants were analyzed with independence tests, with significance set at p < 0.05. Where possible, odds ratios (OR) were calculated using logistic regression. Results: The sample consisted of 60.9% faculty members and 39.1% administrative staff; 42.7% were men and 57.3% were women, with an average age of 41.9 ± 7.6 years. Only 2.7% of participants were aged 60 years or older. The mean serum 25-(OH)D concentration was 19.5 ± 6.8 ng/mL. Altered 25-(OH)D levels were found in 93.4% of participants, with 94.0% showing decreased serum 25-(OH)D concentrations and 1.6% displaying deficiency states. Hypovitaminosis D was associated with sex (OR = 2.40; 95 % CI: 1.3 -5.57; p < 0.05) and sunscreen use (OR = 0.36; 95 % IC: 0.13 -0.99; p < 0.05). Conclusions: Hypovitaminosis D was almost universal among the apparently healthy university workers studied. The findings suggest that both sex and sunscreen use may independently or jointly contribute to hypovitaminosis D in these individuals. Further studies will be required to clarify this interplay.